M2-Macrophage-Derived Exosomes Promote Meningioma Progression through TGF-β Signaling Pathway - Xiao-Hong Fu; Jian-Ping Li; Xue-Ying Li; Yan Tan; Min Zhao; Shao-Fu Zhang; Xue-Dong Wu; Jian-Guo Xu (Journal of Immunology Research)
Tumor-associated macrophages (TAMs) have been shown to be an essential component of the tumor microenvironment and facilitate the proliferation and invasion of a variety of malignancies. However, the contribution of TAMs to meningioma progression has not been characterized in detail. In this study, we aimed to discover a novel regulatory pathway by which exosome-mediated M2-polarized macrophages participate in meningioma tumorigenesis and progression. Methods. First, the distribution and functional phenotype of macrophages in meningioma tissues were assessed by immunohistochemistry. Macrophage-derived exosomes (MDEs) were characterized, and further cell coculture experiments were performed to explore the effects of M2-MDEs on the proliferation, migration, and invasion of meningioma cells. RNA sequencing was used to analyze the transcriptomic signatures in meningioma cells treated with M2-MDEs. Three-dimensional tumorspheres and xenograft tumor models were used to evaluate the effects of M2-MDEs on meningioma tumorigenesis and development. Results. We found that M2 macrophages were enriched in meningioma tissue. Coculture with meningioma cells induced the M2 polarization of macrophages. We also found that M2-MDEs were able to significantly promote cell proliferation, cell migration, cell invasion, and tumorigenesis in meningiomas. Bioinformatic analysis suggested that the TGF-β pathway was activated in meningioma cells treated with M2-MDEs. Functional experiments demonstrated that blocking the TGF-β signaling pathway could effectively reverse the tumor-promotive effects mediated by M2-MDEs. Conclusions. Overall, our study showed that M2-MDEs promoted meningioma development and invasion by activating the TGF-β signaling pathway. Targeting exosome-mediated intercellular communication in the tumor microenvironment may be a novel therapeutic strategy for meningioma patients.